The determinants of bank insolvency risk: evidence from Chinese commercial banks - Cheng, Yun (2020)
Insolvency risk is considered when measures the ability of solvent. There are many reasons behind insolvency risk, like huge losses, lack of liquidity or even frauds and scandals, which have a significant effect on reputation of companies. This paper aims to investigate the determinants of insolvency risk in Chinese banking sector and provides some regulatory implications in managing the risk. The proxy in this paper to measure the risk is Z-score (Boyd and Graham 1986). The data was collected from Bankfocus database of 292 Chinese commercial banks from 2011 to 2019. Statistic panel data regression model is built to examine the significance and coefficient of some estimated bank-specific independent variables. Empirical results show that bank profitability, credit growth, bank size, capital adequacy, leverage ratio, bank income diversification, loan loss provision, bank specialization and bank efficiency have significant effect on bank stability. It is expected that the findings could benefit the banking regulator to monitor and control the insolvency risk by setting some predictable regulations and measures.